AKTIFITAS ANTIBAKTERI ACTINOMYCETES YANG DIISOLASI DARI TPA PUTRI CEMPO MOJOSONGO SURAKARTA - Umi Fatmawati (Universitas Sebelas Maret, 2014)
Abstract- Actinomycetes are procaryotic organisms which are found in many habitats, such as: land, water, and plant tissue. They have numerous function for the production of antibiotics and diversity benders to pest and disease in plants. There were many researchers explored new isolates that produces a compound of a novel metabolites. One of them is screening actinomycetes isolated from the soil samples in Putri Cempo Landfill in Surakarta. The isolates obtained by testing the bacterial activity with well diffusion methods on the Gliserol-Yeast Extract media against four pathogenic bacteria, namely: Ralstonia solanacearum, Bacillus subtilis, Escherichia coli, and Staphylococcus aureus. In this research obtained 10 isolates of actinomycetes, three of them have the ability to inhibit bacterial growth of R. solanacearum, one isolate having the power to against Bacillus subtilis, one isolates having the power of an abstruent against Staphylococcus aureus, and two isolates capale in inhibiting the growth of E. coli. The antibacterial activity were characterized from the inhibitory clear zone arround the ccolony of Actinomycetes. These isolates were: PC 12, PC 13 dan PC 15. The inhibitory clear zone were measured showed the power spectrum of the third of the isolates are belong to the broad spectrum due to their diameter of the clear zone is more than 8 mm. Keywords: Actinomycetes, antibacterial activity, Putri Cempo Landfill, Streptomyces sp, clear zone